2021
DOI: 10.21203/rs.3.rs-128934/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enantioselective Access to Dialkyl Amines and Alcohols via Ni-Catalyzed Reductive Hydroalkylations

Abstract: Chiral dialkyl amines and alcohols are ubiquitous in pharmaceuticals, pesticides, natural products and fine chemicals, yet difficult to access due to the challenge to differentiate between the spatially and electronically similar alkyl groups. Herein, we report a nickel-catalyzed enantioselective reductive hydroalkylation of acyl enamines and enol esters with alkyl halides to afford enantioenriched α-branched aliphatic amines and alcohols in good yields with excellent levels of enantioselectivity. The operatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Because a chiral dialkyl carbinamine subunit is found in a wide array of bioactive molecules (e.g., Figure A), the development of efficient methods for its synthesis, particularly catalytic and enantioselective processes, is an important objective in synthetic organic chemistry . A variety of approaches have been described to date, each of which has limitations, including the addition of alkyl nucleophiles to imines of aliphatic aldehydes (limited scope with respect to the nucleophile), the reduction/hydrogenation of imines of unsymmetrical dialkylketones (modest enantioselectivity when the alkyl groups are similar) and enamines, and the hydroamination of olefins (modest regioselectivity for many internal olefins). After our study was completed, several groups independently demonstrated that nickel-catalyzed asymmetric reductive couplings of olefins and alkyl halides can provide access to protected dialkyl carbinamines. …”
Section: Introductionmentioning
confidence: 99%
“…Because a chiral dialkyl carbinamine subunit is found in a wide array of bioactive molecules (e.g., Figure A), the development of efficient methods for its synthesis, particularly catalytic and enantioselective processes, is an important objective in synthetic organic chemistry . A variety of approaches have been described to date, each of which has limitations, including the addition of alkyl nucleophiles to imines of aliphatic aldehydes (limited scope with respect to the nucleophile), the reduction/hydrogenation of imines of unsymmetrical dialkylketones (modest enantioselectivity when the alkyl groups are similar) and enamines, and the hydroamination of olefins (modest regioselectivity for many internal olefins). After our study was completed, several groups independently demonstrated that nickel-catalyzed asymmetric reductive couplings of olefins and alkyl halides can provide access to protected dialkyl carbinamines. …”
Section: Introductionmentioning
confidence: 99%